Constitutional Regulation of Parliamentary Opposition in Jordan: A Comparative Analysis - Al-Dabbas, Ali (Journal of Legal Sciences, 2026)
This study addresses a topic that has become one of the fundamental requirements for the development of the Jordanian constitutional political system and the activation of representative democracy on which this system is based. It does so by clarifying the concept of parliamentary opposition and calling on the constitutional legislator to enhance its role in parliamentary life and activate its participation in legislation and government oversight as one of the effective means of practicing political pluralism. In conducting this study, the researcher relied on a comparative analytical descriptive methodology, through reviewing and analyzing the texts of the Jordanian Constitution and the internal regulations of the House of Representatives and the Senate, and then comparing them with the provisions of the constitutional document and the internal regulations of the parliaments in Morocco and Algeria, as well as best practices adopted in a number of international charters. The study reached several findings, the most important of which are: the Constitution includes clear provisions recognizing the parliamentary opposition as an effective component of the legislative authority and granting it rights that enable it to activate its role in legislation, oversight, and representation within the permanent organs of Parliament, thereby strengthening sound democratic practice in the state. This approach has been adopted in both Morocco and Algeria, while the Jordanian constitutional framework has not introduced significant amendments in this regard. The study recommends that the Jordanian constitutional legislator explicitly stipulate the rights of the parliamentary opposition in the constitutional document and its complementary legislation. It also recommends explicitly guaranteeing the opposition’s role in legislative and oversight functions by granting it the right to propose legislation and to use oversight mechanisms without being limited by majority decisions. In addition, it recommends granting the opposition the right to challenge the constitutionality of laws and clarifying procedures that ensure the effective exercise of this role. It further calls for institutionalizing its representation in the offices of the presidency of Parliament and parliamentary committees in proportion to its representation in the Council.